Preliminary Findings From a Pilot Study of Electric Vehicle Recharging From a Stand-Alone Solar Minigrid - Gammon, Rupert; Sallah, Momodou (Frontiers in Energy Research, 2021)
The symbiosis between smart minigrids and electric mobility has the potential to improve the cost and reliability of energy access for off-grid communities while providing low-carbon transport services. The Solar Taxi project is exploring the commercial viability of using electric vehicles (EVs), recharged by solar minigrids, to provide transport services in off-grid communities. It has therefore initiated a field trial in The Gambia to assess the techno-economic feasibility of integrating sustainable energy and transport infrastructures in sun-rich regions of the Global South. As a dispatchable anchor load, an EV can improve the technical and economic performance of a minigrid by providing provide demand-side response services. In the developing world, rural communities are often among the poorest, and inadequate transport services remain a major barrier to wealth-creation. Some solutions to this situation may be transferrable to island communities, which share similar challenges in terms of access to energy and fuel. The Solar Taxi project uses an electric minivan, operating from the off-grid village of Manduar in The Gambia, where it has access to a minigrid whose 7.5kWp of photovoltaic modules form the roof of a carport that shelters the vehicle when parked. While there, the taxi can recharge, ideally during sunny periods when the photovoltaic array produces surplus power, thus allowing the EV’s battery to recharge while bypassing the minigrid’s own accumulator. This improves system reliability and cost effectiveness, while providing pollution-free energy for the taxi. The Solar Taxi project aims to test different vehicles in a variety of circumstances and this paper outlines the preliminary findings of the first of these trials. Early results suggest that commercial viability is possible in The Gambia and similar parts of Sub-Saharan Africa. Some promising scenarios for commercial viability are identified, which warrant further investigation. It is hoped that these may to encourage the rollout of solar-recharged EVs where the nexus of sustainable energy and transport systems are likely to make the greatest contribution to addressing the UN’s Sustainable Development Goals, by helping to solve the trilemma of providing energy security, social benefit and environmental sustainability in low-income countries.